Impact of new protectionism on international trade liberalization under WTO conditions - Mostefaoui, Ali; Khedir, Leyla; Gherbi, Tarek; Khedir, Okba (The International tax journal, 2025)
This study aims to shed light on a new economic phenomenon known as "new protectionism," which has replaced traditional trade protectionism. Its intensity has increased in the wake of the global financial crisis, evolving and taking on new dimensions as the global economic situation worsens. The economic and trade repercussions of COVID-19 and the Ukraine war serve as prime examples. Key manifestations of this phenomenon include currency wars, new regional blocs, and environmental challenges. All countries should revert to the agreements of the World Trade Organization (WTO) but with an active dispute resolution mechanism. Additionally, there is a need to establish plans for monitoring currency exchange rates globally in coordination with the International Monetary Fund (IMF) and to develop strategies for addressing and mitigating environmental issues. This should be done within a fair international system that protects emerging industries in developing countries while preserving the industrial capabilities of developed nations.